Characterization of a plankton community in a fish farm - Sipauba-Tavares, Lucia Helena; Millan, Rodrigo Ney; Santeiro, Rachel Magalhaes (My University, 2010)
Aim: The objective of this study was to analyze the composition of phytoplankton and zooplankton communities related to the dynamics of a fish farm; Methods: Samples were collected every other day, within a period of twenty consecutive days, during the dry and rainy seasons. Two samples were collected upstream from the fish pond (reservoir); the other four samples were collected in the fish farm area; Results: Rotifera and Chlorophyceae species were found in high densities at almost all sampling sites during both seasons under analysis. The higher phytoplankton species richness from site P3 to P6 was influenced by the management employed within the fish farm. The zooplankton community showed low values of density, species richness and equitability during the dry season; Conclusions: The continuous water flow and the addition of fertilizers (organic and inorganic) in the fish ponds had an influence on the plankton community, leading to a reduction in water quality and Cyanobacteria dominance.